2018
DOI: 10.31234/osf.io/6kvtn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of grit: A multilevel model examination of demographics and school experiences

Abstract: Much of the research on grit has examined its predictive validity toward academic success; however, little research has treated grit as an outcome. This study uses multilevel modeling to examine how student-level demographics, school-level demographics, and students’ experiences in school predict grit. Results demonstrate that students’ experiences in school—including school engagement, relationships with adults and peers, and school culture—and self-reported GPA were most strongly related to grit, ethnicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The findings of this study are not in line with the conclusions of Bennett et al, who stated that ethnic minorities have a higher level of grit (Bennett et al, 2021;Rindflesch et al, 2023). Linnell also concluded ethnic background correlated with levels of grit, albeit weak (Linnell, 2018). This study supports findings that prove there is no difference in the level of interethnic student grit (Choi & Loui, 2015;Lee et al, 2021) The correlation of family socio-economic background with consistency, persistence, and total grit was tested with Spearsman's test.…”
Section: Hypothesis Verificationcontrasting
confidence: 99%
“…The findings of this study are not in line with the conclusions of Bennett et al, who stated that ethnic minorities have a higher level of grit (Bennett et al, 2021;Rindflesch et al, 2023). Linnell also concluded ethnic background correlated with levels of grit, albeit weak (Linnell, 2018). This study supports findings that prove there is no difference in the level of interethnic student grit (Choi & Loui, 2015;Lee et al, 2021) The correlation of family socio-economic background with consistency, persistence, and total grit was tested with Spearsman's test.…”
Section: Hypothesis Verificationcontrasting
confidence: 99%
“…There is evidence in the United States showing a positive correlation between Grit and school motivation, perceived peer support, perceived teacher support, and perceived school safety ( Eskreis-Winkler et al, 2014 ). Students’ experiences in school including school engagement, relationships with adults and peers, school culture, and self-reported GPA were found to be most strongly related to Grit ( Wanzer, 2018 ). Similarly, in our study, we found a positive relationship between Grit and connectedness to school; specifically, in those reporting a satisfactory relationship with teacher and interest in school subjects.…”
Section: Discussionmentioning
confidence: 99%